Redescription of the endangered hypoptopomatine catfish Parotocinclus spilurus (Fowler, 1941) (Siluriformes: Loricariidae) from the upper rio Jaguaribe basin, northeastern Brazil - Ramos,Telton Pedro A. (2016)
Abstract Parotocinclus spilurus (Fowler) was originally described as a species of Plecostomus based on six specimens collected in the rio Salgado, Icó Municipality, Ceará State, northeastern Brazil. Because the original description of P. spilurus is brief and uninformative, a detailed redescription of this endangered species based on the type series and on freshly collected topotypes was made. Data on osteology, intraspecific variation, sexual dimorphism and color pattern in life are presented for the first time, aiming at providing the necessary characters to differentiate the species from its congeners, as well as providing data on the distribution, habitat and conservation.